Synthesis and biological evaluation of novel homochiral carbocyclic nucleosides from 1-amino-2-indanols - Ugliarolo, Esteban Ariel (2012)
New chiral purinyl and 8-azapurinyl carbanucleoside derivatives based on indanol were synthesized from commercial available (1S,2S)-trans-1-amino-2-indanol and (1R,2R)-trans-1-amino-2-indanol using a linear methodology. The antiviral activity and cytotoxicity of these compounds were evaluated against herpes simplex virus type 1 (HSV-1) in Vero cells, bovine viral diarrhea virus (BVDV) in Mardin-Darby bovine kidney (MDBK) cells and hepatitis B virus (HBV) in HepG2 2.2.15 cell line. Three compounds, showed an inhibition of the HBsAg levels similar to reference drug lamivudine. One chloropurinyl nucleoside, derived from the cis- 1-amino-2-indanol, was cytotoxic on MDBK cells and it could be a lead for developing anticancer agents.